Comparison of Stand-alone Lateral Lumbar Interbody Fusion Versus Open Laminectomy and Posterolateral Instrumented Fusion in the Treatment of Adjacent Segment Disease Following Previous Lumbar Fusion Surgery. Issue 24 (15th December 2019) - Louie, Philip K.; Haws, Brittany E.; Khan, Jannat M.; Markowitz, Jonathan; Movassaghi, Kamran; Ferguson, Joseph; Lopez, Gregory D.; An, Howard S.; Phillips, Frank M.
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to compare clinical and radiographic outcomes of patients who underwent stand-alone lateral lumbar interbody fusion (LLIF) to those who underwent posterolateral fusion (PLF) for symptomatic adjacent segment disease (ASD). Summary of Background Data: Recent studies have suggested that LLIF can successfully treat ASD; however, there are no studies to date that compare LLIF with the traditional open PLF in this cohort. Methods: A total of 47 consecutive patients who underwent LLIF or PLF for symptomatic ASD between January 2007 and August 2016 after failure of conservative management were reviewed for this study. Patient-reported outcomes (PROs) were collected on all patients at preoperative, postoperative, and most recent post-operative visit using the Oswestry Disability Index, Visual Analog Scale (VAS)–Back, and VAS–Leg surveys. Preoperative, immediate postoperative, and most recent postoperative radiographs were assessed for pelvic incidence, fusion, intervertebral disc height, segmental and overall lumbar lordosis (LL). Symptomatic ASD was diagnosed if back pain, neurogenic claudication, or lower extremity radiculopathy presented following a previous lumbar fusion. Preoperative plain radiographs were evaluated for evidence of adjacent segment degeneration. Results: A total of 47 patients (23 LLIF, 24 PLF) met inclusion criteria. Operative times ( P < 0.001) and intraoperative blood loss ( P < 0.001) were significantly higher in the PLF group. Patients who underwent PLF were discharged approximately 3 days after the LLIF patients ( P < 0.001). PROs in the PLF and LLIF cohorts showed significant and equivalent improvement, with equivalent radiographic fusion rates. LLIF significantly improve segmental lordosis ( P < 0.001), total LL ( P = 0.003), and disc height ( P < 0.001) from preoperative to immediate postoperative and final follow-up ( P = 0.004, P = 0.019, P ⩽ 0.001, respectively). Conclusion: Although LLIF may provide less perioperative morbidity and shorter length of hospitalization, both techniques are safe and effective approaches to restore radiographic alignment and provide successful clinical outcomes in patients with adjacent segment degeneration following previous lumbar fusion surgery. Level of Evidence: 3 Abstract : Although lateral lumbar interbody fusion may provide less perioperative morbidity and shorter length of hospitalization, both techniques are safe and effective approaches to restore radiographic alignment and provide successful clinical outcomes in patients with adjacent segment degeneration following previous lumbar fusion surgery.